2005
DOI: 10.1021/nl051584b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Deformation Mechanisms in Bone

Abstract: Deformation mechanisms in bone matrix at the nanoscale control its exceptional mechanical properties, but the detailed nature of these processes is as yet unknown. In situ tensile testing with synchrotron X-ray scattering allowed us to study directly and quantitatively the deformation mechanisms at the nanometer level. We find that bone deformation is not homogeneous but distributed between a tensile deformation of the fibrils and a shearing in the interfibrillar matrix between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
236
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(251 citation statements)
references
References 28 publications
15
236
0
Order By: Relevance
“…There is growing evidence that the nanoscale processes that are involved in bone fracture include the relative motion of mineralized collagen fibrils and that the resistance of bone to fracture may depend on the ability of bone to dissipate energy in the interfibrillar matrix during this relative motion. [26][27][28][29][30][31] These same processes may be involved in resistance of bone to the continuing indentation that is measured by the IDI. So, perhaps, it is not surprising that, as shown below in model systems, bone that is more easily fractured has larger IDIs.…”
Section: Indentation Distance Increasementioning
confidence: 99%
“…There is growing evidence that the nanoscale processes that are involved in bone fracture include the relative motion of mineralized collagen fibrils and that the resistance of bone to fracture may depend on the ability of bone to dissipate energy in the interfibrillar matrix during this relative motion. [26][27][28][29][30][31] These same processes may be involved in resistance of bone to the continuing indentation that is measured by the IDI. So, perhaps, it is not surprising that, as shown below in model systems, bone that is more easily fractured has larger IDIs.…”
Section: Indentation Distance Increasementioning
confidence: 99%
“…30 We have recently shown that shearing in the interfibrillar matrix is also a fundamental deformation mechanism in bone. 6 The helicoidal arrangement of fibrils in osteons is seen by the average angle over all cholesteric layers being different from zero ͑Fig. 3͒.…”
Section: Discussionmentioning
confidence: 99%
“…4 Different approaches have been taken in solving these questions on different length scales, from static structure investigations 5 to in situ mechanical testing. 6 Compact bone, which is found in the cylindrical shells of most long bones in vertebrates, consists of lamellae that are cylindrically wrapped around blood vessels ͑Haversian systems or secondary osteons͒. These secondary osteons, whose mechanical properties are crucial to the structural stability of the entire bone, form during bone remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the young age, no secondary osteons ("Haversian systems") are expected to be present. Although a detailed quantitative description of the deformation mechanisms of bone at the nanoscale remains unclear, several mechanisms have been proposed [1,[7][8][9]. In addition, the influence of the environment on the mechanical properties of compact bone is still not well understood.…”
Section: Introductionmentioning
confidence: 99%